Citizen Rights in a Critical Juncture: Comparing the EU and ASEAN Legal Response in the time of the COVID-19 Pandemic - Nur, Asrul Ibrahim (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
The article's primary objective is to explore and compare the legal instrument adopted by regional organisations, specifically the EU and ASEAN, to impose restrictions on free movement rights during the COVID-19 Pandemic. This article uses hard and soft law classifications to denote the great number of types and forms of legal instruments. Furthermore, this article aims to explain the pattern of regional organisations adopting legal tools to govern restrictions on free movement rights. Legal research methodologies analyse legal instruments from the EU and ASEAN's official legal databases with doctrinal and comparative perspectives. The study's findings revealed two distinct trends of adopting various types of legal instruments by the EU and ASEAN. Additionally, the choice of this type of legal instrument has ramifications for guaranteeing the practical application of citizen rights, particularly the right to freedom of movement.